Type III chaperones & Co in bacterial plant pathogens: a set of specialized bodyguards mediating effector delivery - Lohou, David; Lonjon, Fabien; Genin, Stéphane; Vailleau, Fabienne (Frontiers in Plant Science, 2013)
Gram-negative plant pathogenic bacteria possess a type III secretion system (T3SS) to inject bacterial proteins, called type III effectors (T3Es), into host cells through a specialized syringe structure. T3Es are virulence factors that can suppress plant immunity but they can also conversely be recognized by the plant and trigger specific resistance mechanisms. The T3SS and injected T3Es play a central role in determining the outcome of a host-pathogen interaction. Still little is known in plant pathogens on the assembly of the T3SS and the regulatory mechanisms involved in the temporal control of its biosynthesis and T3E translocation. However, recent insights point out the role of several proteins as prime candidates in the role of regulators of the type III secretion (T3S) process. In this review we report on the most recent advances on the regulation of the T3S by focusing on protein players involved in secretion/translocation regulations, including type III chaperones (T3Cs), type III secretion substrate specificity switch (T3S4) proteins and other T3S orchestrators.